Hydrogen‐Generating Magnesium Alloy Seed Strand Sensitizes Solid Tumors to Iodine‐125 Brachytherapy - Pan Hu; Letao Lin; Guanyu Chen; Dengyao Liu; Huanqing Guo; Meigui Xiao; Zhihui Zhong; Guang Yang; Bingchen Xu; Dongcun Huang; Sheng Peng; Yong Li; et al. (Advanced Science)
Abstract Radioactive iodine‐125 (125I) seed implantation, a brachytherapy technique, effectively kills tumor cells via X‐rays and gamma rays, serving as an alternative therapeutic option following the failure of frontline treatments for various solid tumors. However, tumor radioresistance limits its efficacy. Hydrogen gas has anticancer properties and can enhance the efficacy of immunotherapy. However, its role in radiotherapy sensitization has rarely been reported. Many current hydrogen delivery methods involve hydrogen‐generating nanomaterials, such as magnesium‐based nanomaterials. This study introduces an AZ31 magnesium alloy 125I seed strand (termed AMASS) with pH‐dependent slow‐release hydrogen characteristics and excellent mechanical properties. AMASS can be implanted into tumors via minimally invasive surgery, releasing hydrogen around the 125I seeds. In vitro experiments showed that hydrogen from AMASS degradation significantly inhibited tumor proliferation, increased apoptosis, disrupted redox homeostasis and mitochondrial membrane potential, reduced adenosine triphosphate levels, and induced DNA damage due to 125I radiation. In mouse xenograft and rabbit liver tumor models, hydrogen from AMASS showed superior therapeutic effects compared with 125I seeds alone, with no noticeable side effects. In addition, AMASS has a uniform radiation dose distribution and simple implantation. Therefore, hydrogen from AMASS enhanced 125I seed efficacy, supporting the further promotion and application of 125I seed implantation in cancer therapy.